2005
DOI: 10.1557/proc-0887-q05-03
|View full text |Cite
|
Sign up to set email alerts
|

Electron work function at grain boundary and the corrosion behavior of nanocrystalline metallic materials

Abstract: Due to their high grain boundary density, nanocrystalline materials possess unusual mechanical, physical and chemical properties. Extensive research on nanocrystalline materials has been conducted in recent years. Many studies have shown that corrosion, one of important properties of nanocrystalline materials, is crucial to their applications. In this article, the activity of electrons at grain boundaries of metallic surfaces is analyzed based the electron work function (EWF), the minimum energy required to at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Some of the studies showed than nanocrystalline structure lowers EFW of the alloy, leading to the higher reaction rate and also easier formation of passive film [69,198]. Attempts were made to link EFW of alloy with the adhesive strength of the passive film and reported that higher reactivity of nanocrystalline surfaces leads to enhanced adhesion strength between passive film and the alloy surface due to the increase in the electron activity at grain boundaries and possible pegging of the passive film into the grain boundaries [69,235].…”
Section: Increased Surface Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the studies showed than nanocrystalline structure lowers EFW of the alloy, leading to the higher reaction rate and also easier formation of passive film [69,198]. Attempts were made to link EFW of alloy with the adhesive strength of the passive film and reported that higher reactivity of nanocrystalline surfaces leads to enhanced adhesion strength between passive film and the alloy surface due to the increase in the electron activity at grain boundaries and possible pegging of the passive film into the grain boundaries [69,235].…”
Section: Increased Surface Activitymentioning
confidence: 99%
“…Initially, it was believed that nanocrystalline materials (including SS), owing to a high surface energy, may have displayed inferior corrosion resistance [69]. However, in recent years, the corrosion resistance of nanocrystalline SS produced by various routes has been investigated and the reported data presents a range of differing corrosion behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic deformation results in an increase of the dislocation density which also affects local surface work function and hence the electrochemical potential [10]. The Electron Work Function (EWF) reflects the electron activity [10,11] and is the minimum energy required to remove electrons from inside a metal to a position far away from the surface on the atomic scale, but still close to the metal to be influenced by ambient electric fields [10][11][12][13][14][15][16][17]. It is not a material property but characteristic of the surface and is sensitive to pre-existing deformation, surface oxide layers, roughness, temperature, and adsorbents [15,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…An increase of plastic strain and strain rate decreased the EWF hence the change in EWF could be attributed to the dislocation density in the microstructure. Furthermore, it was demonstrated that at grain boundaries the EWF decreased, in contrast to the grain interior of nanostructure materials, indicating that at such sites the electron activity is high with the result that the surface became more electrochemically reactive [11]. Such an increase in electrochemical reactivity affects local and overall corrosion performance of the material [11].…”
Section: Introductionmentioning
confidence: 99%
“…The effective role of the grain-size refinement on the enhancement of the corrosion behavior has been previously reported [58][59][60][61]. It has been shown that the ultrafine grains improve the activity of electrons at grain boundaries leading to the decrease in the electron work function [62]. Thus, the surface of the UFG alloy becomes more electrochemically reactive giving rise to the rapid formation of a mechanically strong and stable passive layer.…”
Section: Discussionmentioning
confidence: 94%